The Amphibian Diversity of Bukit Jana, Taiping, Perak - Shahriza Shahrudin; Ibrahim Jaafar (Tropical Life Sciences Research, 2012)
The study on the amphibian fauna of Bukit Jana, Taiping, Perak was carried out from January 2009 until December 2010 with a total of 12 nights of observation. Twenty four species of frogs from 14 genera and 6 families were recorded to inhabit the Bukit Jana areas. Seven commensal species were found around human habitations near the foothill whereas the others are typical forest frogs found mostly near the rivers, streams and forest floor. This is the first amphibian checklist of Bukit Jana, Perak and it contributed 22% out of 107 species of frogs that are recorded to inhabit Peninsular Malaysia. Kajian terhadap fauna amfibia di Bukit Jana, Taiping, Perak telah dijalankan dari Januari 2009 sehingga Disember 2010; pemerhatian dilakukan pada 12 malam. Dua puluh empat spesies katak dari 14 genera dan 6 famili telah direkodkan menghuni kawasan Bukit Jana. Tujuh spesies komensal telah dijumpai sekeliling habitat manusia, berdekatan dengan kaki bukit manakala katak hutan biasa kebanyakannya dijumpai berdekatan dengan sungai, anak sungai dan lantai hutan. Ini merupakan senarai semak pertama untuk amfibia Bukit Jana, Perak dan didapati menyumbang sebanyak 22% daripada 107 spesies katak yang telah direkodkan berhabitat di Semenanjung Malaysia.